Assessment of the prevalence of H1N1 in Brazil between 2016 and 2020 and the importance of vaccination as a strategy to reduce cases (Research, Society and Development, 2022)
In April 2009, there was an outbreak of illness caused by the novel influenza A(H1N1) virus, which has a rapid power of dissemination. Initially it was known as “swine flu”, due to the genetic event that caused the emergence of the new pandemic subtype resulting from the genetic recombination of swine, avian and human viruses, having a high potential for spread among humans. In this way, the present study is based on the construction of an integrative bibliographical review, using the PRISMA-type methodology, aiming at evaluating the prevalence of influenza A(H1N1) in Brazil between 2016 and 2020 and the impact of vaccination as a strategy to reduce the two cases. The study eligibility criteria for this research will result in 11 studies relevant to the discussion process. Desses, representatively, 1 from Scielo, 3 from Pubmed and 7 from Sciencedirect. As it was possible to identify that influenza A/H1N1 is an acute infectious disease with high morbidity and mortality, with these prevalent rates in patients, children, pregnant women and carriers of chronic diseases. However, it was found that vaccination was effective in preventing the evolution of disease for its most severe form, and the development of new pathologies, as well as avoiding hospitalizations, as well as medical expenses.